2022
DOI: 10.1002/jcla.24406
|View full text |Cite
|
Sign up to set email alerts
|

LINC00941 promoted in vitro progression and glycolysis of laryngocarcinoma by upregulating PKM via activating the PI3K/AKT/mTOR signaling pathway

Abstract: Background LINC00941 has been proved to be related to various tumors, but its relationship with laryngocarcinoma remains vague. Methods LINC00941 expression in laryngocarcinoma tumor and laryngocarcinoma cells was determined by real time‐quantitative polymerase chain reaction (RT‐qPCR). Besides, the five‐year survival of laryngocarcinoma patients with different LINC00941 expression was analyzed with Kaplan–Meier survival analysis, and the clinical characteristics of laryngocarcinoma patients were also recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…It was also identified that ATF3 transcription factor enhances LINC00941 expression. Additionally, LINC00941 was shown to promote glycolysis and laryngocarcinoma progression through the PI3K/AKT/mTOR signaling pathway and its upregulation of PKM ( 102 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was also identified that ATF3 transcription factor enhances LINC00941 expression. Additionally, LINC00941 was shown to promote glycolysis and laryngocarcinoma progression through the PI3K/AKT/mTOR signaling pathway and its upregulation of PKM ( 102 ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 38 ] PI3K-Akt is a unique master regulator of various cancers and can also regulate the occurrence and development of laryngeal cancer. [ 39 ] As a tumor promoter, the TNF signaling pathway plays an important role in regulating the occurrence and metastasis of tumors. [ 40 ] Studies have shown that by regulating the TNF signaling pathway, Protein Tyrosine Phosphatase Non-Receptor Type 2 is highly expressed in laryngeal cancer and can regulate the proliferation of laryngeal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This singular transcript feature of the gene highlights its unique molecular characteristics in GI cancer studies. Recently, a large number of studies have shown that it is involved in the progression of various tumors [27][28][29][30][31][32][33][34], particularly in GI malignancies [35][36][37][38][39][40][41][42][43][44][45][46][47]. Dysregulated expression of LINC00941 has been observed in GI tumors [35,43,44,46].…”
Section: Ivyspringmentioning
confidence: 99%